PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DEVIDEN - Bella Novianti Rais; Hendra F. Santoso (Jurnal Akuntansi, 2018)
The purpose of research is to know the factors that influencing the dividend policy. The factors cover Managerial Ownership (KM), Institutional Ownership (KI), Profitability (ROI) and Company Size (SZ).The data used is secondary data in the annual financial statements Manufacturing Company. Sampling in this study using purposive sampling method. With this method, acquired 135 companies that serve as the research sample. Data analysis method used is descriptive analysis, Classical Assumption Test, Multiple Linear Regression Analysis and Testing Hypotheses. The results showed that Managerial Ownership,Institutional Ownership, Profitability does not have a significant effect on deviden policy and Company Size has a significant influence on deviden policy. Keywords: Managerial Ownership (KM), Institutional Ownership (KI), Profitability (ROI), Company Size (SZ) and Dividend Payout Ratio (DPR).